The Influence of Income, Taxpayer Awareness, and Tax Services on Taxpayer Compliance at PT Rajawali Assa Mandiri - Sudono, Agus; Sundjoto, Sundjoto; Rahayu, Sri; Fitrianty, Rifda (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Tax revenue plays a crucial role in supporting national development, making taxpayer compliance an essential aspect of achieving Indonesia’s fiscal goals. However, compliance among employee taxpayers remains inconsistent due to diverse financial capacities, behavioral awareness levels, and the perceived quality of tax services. This study examines the influence of income, taxpayer awareness, and tax service quality on employee taxpayer compliance at PT Rajawali Assa Mandiri. A quantitative explanatory research design was applied, using a structured questionnaire distributed to employees selected through purposive sampling based on their status as active taxpayers. Multiple linear regression analysis was conducted to assess both partial and simultaneous relationships among the variables. The results reveal that income, taxpayer awareness, and tax service quality significantly contribute to employee taxpayer compliance, indicating that compliance behavior is shaped not only by economic ability but also by psychological readiness and administrative support. Although the predictive model demonstrates meaningful explanatory power, a portion of compliance variance remains influenced by other behavioral and organizational factors beyond the scope of this study. These findings suggest the need for integrated interventions that reinforce taxpayer education, enhance service accessibility, and align taxation policies with employee financial conditions. The study offers practical insight for government institutions and organizations in strengthening voluntary compliance to improve national tax revenue sustainability.